PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Mangkusuryo, Yusuf; Jati, Ahmad Waluya (Jurnal Reviu Akuntansi dan Keuangan)
This study aimed to determine the effect of Good Corporate Governance mechanism towardearnings management that is proxied with discretionary accruals (DTA). The GCG mechanismis proxied with managerial ownership (KM), institutional leadership (KI), independent board ofcommissioner (DKI) and independent audit committee (KAI). The sample used in this studywere 11 companies registered in CGPI for three years starting from 2013 to 2015.To knowwhether the above GCG variables have an effect on earnings management, multiple linearregression test using SPSS 2.1 program. The test results show that only managerial ownershipvariables has significantly influence to earnings management. While other variables such asinstitutional ownership (KI), independent board of commissioner (DKI), and independent auditcommittee (KAI) have no significant effect to earnings management.Keyword: Good Corporate Governance, managerial ownership, institusional leadership, independent board of commisioner, independent audit committee, earning management.